2008
DOI: 10.1007/s10764-008-9301-6
|View full text |Cite
|
Sign up to set email alerts
|

How Reliable are Density Estimates for Diurnal Primates?

Abstract: Primate population assessments provide the basis for comparative studies and are necessary prerequisites in determining conservation status. The most widely used assessment method is line transect sampling, which generates systematic data quickly and comparatively inexpensively. In contrast, the presumably most reliable method is long-term monitoring of known groups, which is both slow and costly. To assess the reliability of various analytical methods, we compared group and population densities for white-hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 21 publications
0
37
0
2
Order By: Relevance
“…Empirical data support the use of A-O estimates. Based on a number of studies from 10 primate species (Struhsaker 1975, National Research Council 1981, Chapman et al 1988, Fashing and Cords 2000, Hassel-Finnegan et al 2008) that contrasted actual density derived from long-term records of home ranges and density estimates derived from A-O estimates and perpendicular distance (see Marshall et al [2008] for a discussion of census methods for primates), the A-O estimate overestimated density for six of the 10 species and underestimated it in four of the 10 species, while for all species the perpendicular estimates overestimated the actual density, often by .100% (mean percentage over ¼ 104%; Fig. 1).…”
Section: Primate Group Densitymentioning
confidence: 99%
“…Empirical data support the use of A-O estimates. Based on a number of studies from 10 primate species (Struhsaker 1975, National Research Council 1981, Chapman et al 1988, Fashing and Cords 2000, Hassel-Finnegan et al 2008) that contrasted actual density derived from long-term records of home ranges and density estimates derived from A-O estimates and perpendicular distance (see Marshall et al [2008] for a discussion of census methods for primates), the A-O estimate overestimated density for six of the 10 species and underestimated it in four of the 10 species, while for all species the perpendicular estimates overestimated the actual density, often by .100% (mean percentage over ¼ 104%; Fig. 1).…”
Section: Primate Group Densitymentioning
confidence: 99%
“…Line-transect distance sampling proved to be particularly suitable for estimating the density and and Pintor 1985; Chapman et al 1988;García 1993;Peres 1999;Brugière and Fleury 2000;Plumptre and Cox 2006;Marshall et al 2008). In this sampling method, observers walk along a series of relatively straight transect lines, and record, for each encounter with the study objects, the perpendicular distance(s) from the line to each object detected or to the estimated center of the group formed by all objects detected (Whitesides et al 1988;Hassel-Finnegan et al 2008;Marshall et al 2008). These distances are used to estimate a detection function (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We encourage future projects to use Distance in establishing the maximum listening radius in combination with the featured formula to determine a density estimate for hylobatids (Brockelman and Ali 1987;Phoonjampa et al 2011). Distance is an important tool for surveying primate species because it can be used in different environments and allows for standardization between surveys across different habitats (Hassel-Finnegan et al 2008). Having demonstrated that point transect and distance analysis can be used with triangulation data, we encourage future and perhaps even retrospective distance analysis of gibbon data from other sites to elucidate trends in the accuracy of this new method.…”
Section: Discussionmentioning
confidence: 99%